2003
DOI: 10.1095/biolreprod.102.012880
|View full text |Cite
|
Sign up to set email alerts
|

Immunocontraception Is Induced in BALB/c Mice Inoculated With Murine Cytomegalovirus Expressing Mouse Zona Pellucida 31

Abstract: Immunocontraception, the prevention of oocyte fertilization through immunological means, could potentially be used to control plaguing mouse populations in Australia. This paper describes the construction of a mouse-specific betaherpesvirus, murine cytomegalovirus, which has been engineered to express the murine zona pellucida 3 (ZP3) gene. A single inoculation of this recombinant virus resulted in almost complete infertility, persistent anti-ZP3 antibody production, and profound changes to ovarian morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 21 publications
5
89
1
1
Order By: Relevance
“…A previous study suggested that CMV infection was sufficient to break immune tolerance to a self-antigen (43). In this study, we demonstrated that immunization with recombinant MCMV vectors that expressed a foreign antigen (MCMV-OVA) or a modified melanoma antigen gp100 (MCMV-gp100KGP) overcame immune tolerance and the tumor immunosuppressive milieu and elicited a high frequency of longlasting and polyfunctional tumor antigen-specific CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 68%
“…A previous study suggested that CMV infection was sufficient to break immune tolerance to a self-antigen (43). In this study, we demonstrated that immunization with recombinant MCMV vectors that expressed a foreign antigen (MCMV-OVA) or a modified melanoma antigen gp100 (MCMV-gp100KGP) overcame immune tolerance and the tumor immunosuppressive milieu and elicited a high frequency of longlasting and polyfunctional tumor antigen-specific CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 68%
“…The MCMV transfer plasmid vector pH3L contains the entire 7161 bp HindIII L fragment of MCMV strain K181 inserted into plasmid pGEM11 (Lloyd et al 2003). The 79 bp HpaI fragment of pH3L within the MCMV ie2 gene was removed and replaced by a NotI linker to produce pH3LN.…”
Section: Construction Of MCMV Transfer Plasmid Vectorsmentioning
confidence: 99%
“…Recombinant viruses provide one means of delivery of contraceptive antigens and are effective in reducing the fertility of mice (Jackson et al 1998, Lloyd et al 2003. These vaccines have employed female gamete antigens and affect the fertility of female mice only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…128 Infection of mice with recombinant cytomegalovirus (mouse-specific β herpes virus) expressing mouse ZP3 also led to permanent infertility, principally due to induction of the ovarian autoimmune pathology leading to progressive oocyte depletion. 129,130 The idea of developing host-specific live vector-based contraceptive vaccine to control the population of pests such as wild rats and rabbits in Australia was to release these live vector contraceptive vaccines in the environment so that recombinant virus gets transmitted from one animal to another, thereby leading to effective management of their population. However, one of the limitations of this approach is that recombinant virus has lower infectivity as compared with wild type.…”
Section: Live Vector-based Contraceptive Vaccines Expressing Zp Proteinsmentioning
confidence: 99%